Measuring the effect of enhanced cleaning in a UK hospital: a prospective cross-over study - Dancer, Stephanie J; White, Liza F; Lamb, Jim; Girvan, E Kirsty; Robertson, Chris (BMC medicine, 2009)
Background Increasing hospital-acquired infections have generated much attention over the last decade. There is evidence that hygienic cleaning has a role in the control of hospital-acquired infections. This study aimed to evaluate the potential impact of one additional cleaner by using microbiological standards based on aerobic colony counts and the presence of Staphylococcus aureus including meticillin-resistant S. aureus . Methods We introduced an additional cleaner into two matched wards from Monday to Friday, with each ward receiving enhanced cleaning for six months in a cross-over design. Ten hand-touch sites on both wards were screened weekly using standardised methods and patients were monitored for meticillin-resistant S. aureus infection throughout the year-long study. Patient and environmental meticillin-resistant S. aureus isolates were characterised using molecular methods in order to investigate temporal and clonal relationships. Results Enhanced cleaning was associated with a 32.5% reduction in levels of microbial contamination at hand-touch sites when wards received enhanced cleaning ( P < 0.0001: 95% CI 20.2%, 42.9%). Near-patient sites (lockers, overbed tables and beds) were more frequently contaminated with meticillin-resistant S. aureus / S. aureus than sites further from the patient ( P = 0.065). Genotyping identified indistinguishable strains from both hand-touch sites and patients. There was a 26.6% reduction in new meticillin-resistant S. aureus infections on the wards receiving extra cleaning, despite higher meticillin-resistant S. aureus patient-days and bed occupancy rates during enhanced cleaning periods ( P = 0.032: 95% CI 7.7%, 92.3%). Adjusting for meticillin-resistant S. aureus patient-days and based upon nine new meticillin-resistant S. aureus infections seen during routine cleaning, we expected 13 new infections during enhanced cleaning periods rather than the four that actually occurred. Clusters of new meticillin-resistant S. aureus infections were identified 2 to 4 weeks after the cleaner left both wards. Enhanced cleaning saved the hospital £30,000 to £70,000. Conclusion Introducing one extra cleaner produced a measurable effect on the clinical environment, with apparent benefit to patients regarding meticillin-resistant S. aureus infection. Molecular epidemiological methods supported the possibility that patients acquired meticillin-resistant S. aureus from environmental sources. These findings suggest that additional research is warranted to further clarify the environmental, clinical and economic impact of enhanced hygienic cleaning as a component in the control of hospital-acquired infection.